The combined effect of ultrasound treatment and papain on the quality properties of beef - Ahmad Danial, A.N.; Ismail, N.A.; Nor-Khaizura, M.A.R.; Azman, E.M.; Noranizan, M.A.; Ismail-Fitry, M.R. (Rynnye Lyan Resources, 2024)
Individual ultrasound treatment or adding exogenous enzyme treatment such as papain has been successfully proven to not only marinate but tenderise the meat. Incorporating both treatments at the same time could further tenderise the meat but the quality of the meat might be compromised. Hence, this study aimed to investigate the effect of ultrasound treatment coupled with papain solution on the quality properties of meat. Four different treatments were carried out on the meat samples; control (C), papain treated (P), ultrasound treated (US), and a combination of papain and ultrasound treated (USP). Meat treated with USP did not affect the physicochemical properties of the meat as no significant difference was found in water holding capacity (WHC), cooking loss and pH. Moreover, USP treatment was found to have effects on textural properties of the meat samples as positive linear relationships between the hardness of the treated meat with work of shear were found via Pearson correlation analysis. This is in line with the findings on the microstructure of the treated meat samples where tenderised meat samples exhibited disrupted muscle fibre. Thus, incorporating papain and ultrasound together improved the quality texture of the meat.